2015
DOI: 10.1038/ncomms10206
|View full text |Cite
|
Sign up to set email alerts
|

Exome-wide association analysis reveals novel coding sequence variants associated with lipid traits in Chinese

Abstract: Blood lipids are important risk factors for coronary artery disease (CAD). Here we perform an exome-wide association study by genotyping 12,685 Chinese, using a custom Illumina HumanExome BeadChip, to identify additional loci influencing lipid levels. Single-variant association analysis on 65,671 single nucleotide polymorphisms reveals 19 loci associated with lipids at exome-wide significance (P<2.69 × 10−7), including three Asian-specific coding variants in known genes (CETP p.Asp459Gly, PCSK9 p.Arg93Cys and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 58 publications
4
84
0
Order By: Relevance
“…Since the physiopathology of NAFLD is tightly related to the metabolic syndrome, a link between rs738409[G] and the parameters that define the metabolic syndrome was a likely hypothesis. Indeed, some authors have observed an association between PNPLA3 and insulin resistance [20], and lower fasting triglycerides in severely obese patients and in individuals from Asian descent [21,22]. However, the vast majority of studies have shown that PNPLA3 was not associated with BMI, serum lipid, or glycaemic traits [6,13,23].…”
Section: Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Since the physiopathology of NAFLD is tightly related to the metabolic syndrome, a link between rs738409[G] and the parameters that define the metabolic syndrome was a likely hypothesis. Indeed, some authors have observed an association between PNPLA3 and insulin resistance [20], and lower fasting triglycerides in severely obese patients and in individuals from Asian descent [21,22]. However, the vast majority of studies have shown that PNPLA3 was not associated with BMI, serum lipid, or glycaemic traits [6,13,23].…”
Section: Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Discovery cohort The discovery stage involved a total of 5640 Southern Han Chinese participants (3652 cases and 1988 controls) from the HKU-TRS cohort who participated in a previous exome-chip association study for blood lipid traits [2]. The study participants were recruited from the Hong Kong West Diabetes Registry (HKWDR) [14], the Hong Kong Cardiovascular Risk Factor Prevalence Study (CRISPS) [15] and the Hong Kong Chinese coronary artery disease (CAD) cohort.…”
Section: Participantsmentioning
confidence: 99%
“…All participants were recruited from these clinic-based or community-based studies conducted at the Queen Mary Hospital, Hong Kong, People's Republic of China. Details of the corresponding cohorts have been previously reported [2]. Type 2 diabetes cases were defined as meeting at least one of the following criteria: fasting plasma glucose (FPG) ≥ 7 mmol/l, 2 h glucose during OGTT ≥ 11.1 mmol/l, taking glucose-lowering agents or physician-diagnosed diabetes.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations